Fish for the city: meta-analysis of archaeological cod remains and the growth of London's northern trade. (1st June 2014) - Orton, David C.; Morris, James; Locker, Alison; Barrett, James H.
Abstract : The growth of medieval cities in Northern Europe placed new demands on food supply, and led to the import of fish from increasingly distant fishing grounds. Quantitative analysis of cod remains from London provides revealing insight into the changing patterns of supply that can be related to known historical events and circumstances. In particular it identifies a marked increase in imported cod from the thirteenth century AD. That trend continued into the fifteenth and sixteenth centuries, after a short downturn, perhaps attributable to the impact of the Black Death, in the mid fourteenth century. The detailed pattern of fluctuating abundance illustrates the potential of archaeological information that is now available from the high-quality urban excavations conducted in London and similar centres during recent decades.